2021
DOI: 10.1093/eurjpc/zwab011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and impact on cardiovascular events and mortality in patients with chronic coronary syndromes, across multiple geographical regions and ethnicities

Abstract: Background In contrast with the setting of acute myocardial infarction, there are limited data regarding the impact of diabetes mellitus on clinical outcomes in contemporary cohorts of patients with chronic coronary syndromes. We aimed to investigate the prevalence and prognostic impact of diabetes according to geographical regions and ethnicity. Methods and results CLARIFY is an observational registry of patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
0
7
0
3
Order By: Relevance
“…The effect sizes of these scores on the circulating protein levels were all positively correlated with that of the PGS T2D_gw (p-value < 0.05, Figure 1C ), supporting the epidemiological observation that cardiometabolic diseases are highly interconnected. 34,35 However, for select proteins, the directions of effect of the T2D T2D_gw on circulating levels were in fact opposite when compared to the effects of another PGS (e.g., the effect of PGS T2D_gw and PGS BMI on TIMP4 levels, see Supplementary Information , supplementary figure 18, and Supplementary Table 8 ), likely reflecting more complicated relationships such as compensatory responses. 36–38 In the case of the partitioned scores, the correlation patterns seem to point to proteomic mechanisms that explain their differential associations with T2D comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…The effect sizes of these scores on the circulating protein levels were all positively correlated with that of the PGS T2D_gw (p-value < 0.05, Figure 1C ), supporting the epidemiological observation that cardiometabolic diseases are highly interconnected. 34,35 However, for select proteins, the directions of effect of the T2D T2D_gw on circulating levels were in fact opposite when compared to the effects of another PGS (e.g., the effect of PGS T2D_gw and PGS BMI on TIMP4 levels, see Supplementary Information , supplementary figure 18, and Supplementary Table 8 ), likely reflecting more complicated relationships such as compensatory responses. 36–38 In the case of the partitioned scores, the correlation patterns seem to point to proteomic mechanisms that explain their differential associations with T2D comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…While there are studies that have established the prevalence of T2D in the Middle East and Africa, [21][22][23][24][25][26] there is limited information on the prevalence of eASCVD or on high/very high ASCVD risk in patients with T2D in this region. 3,[27][28][29][30][31] The CAPTURE study estimated the prevalence of ASCVD among patients with T2D across 13 countries from five continents and showed that one in three adults with T2D have established CVD, of which 9/10 had ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…За даними реєстрів та рандомізованих клінічних випробувань, від 29 до 41% хворих на стабільну ішемічну хворобу серця (ІХС) мають цукровий діабет (ЦД) [1,2,3] Серед молекул адгезії, що експресуються в атеромі та опосередковують проникнення моноцитів і лімфоцитів до ендотелію та подальшу їх міграцію в атеросклеротичну бляшку, найбільша частка (82%) припадає на судинну молекулу клітинної адгезії 1 (Vascular cell adhesion molecule-1 (VCAM-1)), яка розглядається як хороший маркер для виявлення наявних атеросклеротичних уражень, а також для раннього виявлення активованого ендотелію з ризиком утворення бляшок [12]. У клінічних дослідженнях активно вивчається розчинна форма VCAM-1 (soluble VCAM-1 (sVCAM-1)), що вивільняється в судинне русло і вважається індикатором судинного запалення та активації ендотелію [13,14].…”
Section: Abstract Vascular Cell Adhesion Molecule-1 Levels In Patient...unclassified